Textual Trappings in Emily Dickinson's Selected Poems - Abdul Ameer, Sahar (Opción, 1970)
Dickinson´s poetry is unique for several reasons. For her poemscan be regarded very private .She was interested in the innermostworld of the human mind. Thus one of the foremost aspects of herpoetry is the ability to condense a great theme or an intenseinvolvement into a few lines. Both the structure as well as poeticdiction of Dickinson were exceptionally inventive in her lifetime. Shehighlighted her poetry by a distinctive use of capitalization, and ofpunctuations she used primarily dashes. Such use was so innovativeand helpful to the poet to interpret her intention. It also functions asproviding different interpretations to the poem leading the reader tohave a very vivid and active role in these interpretations. This alsomight be due to her own personality as well as the sensitive attitudesshe has towards issues in life and her desire to add ambiguity to herpoems that are supposed to talk about her own experiences and thesituations she lived in. Thus, Dickinson’s poetic novelty is due to thespiritual forces of the world around her. Such a thing led her to have anacceptance of life as it is and gave her a distinctive style among whichis the use of dashes as well as the intended capitalization to reflect ina very distinctive and unique way her intention as well as herconviction about life and the world around her. A conviction that ismore personal and more of hers as well.